2019
DOI: 10.1038/s41390-019-0420-x
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive noxious stimuli during early development affect acute and long-term mechanical sensitivity in rats

Abstract: BACKGROUND: Prematurely born infants are frequently exposed to painful procedures in the neonatal intensive care unit, causing changes to the development of the nervous system lasting into adulthood. The current study aims to study acute and long-term consequences of neonatal repetitive noxious stimulation. METHODS: Rat pups received either 4 or 10 unilateral needle pricks per day, while control littermates received 4 or 10 tactile stimuli in the first postnatal week. Behavioural sensitivity was assessed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
(63 reference statements)
2
19
0
Order By: Relevance
“…On the other hand, when we analyzed mechanical hyperalgesia, we observed a decrease in pain sensitivity only in adulthood, for both males and females, between the anoxia and control groups. The present results are supported by studies that evaluated nociceptive responses at adulthood, after neonatal noxious stimuli (Davis & Burman, 2020;Ririe et al, 2003;van den Hoogen et al, 2020). In addition, a study conducted by Davis and Burman (2020) revealed that neonatal pain enhances subsequent fear conditioning in adolescent female rats and creates an age-and sexindependent tactile response.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, when we analyzed mechanical hyperalgesia, we observed a decrease in pain sensitivity only in adulthood, for both males and females, between the anoxia and control groups. The present results are supported by studies that evaluated nociceptive responses at adulthood, after neonatal noxious stimuli (Davis & Burman, 2020;Ririe et al, 2003;van den Hoogen et al, 2020). In addition, a study conducted by Davis and Burman (2020) revealed that neonatal pain enhances subsequent fear conditioning in adolescent female rats and creates an age-and sexindependent tactile response.…”
Section: Discussionsupporting
confidence: 82%
“…The most commonly used species are rodents; however, there are reports of other species being used. For example, piglets who undergo tail docking (P3 or P63) have longterm peripheral mechanical hyperalgesia (tail stump) (212) and distinctive changes in gene expression up to 16 weeks following the procedure (213).…”
Section: Models To Study the Effects Of Early Life Pain On Pain Models To Study The Effects Of Early Life Pain On Pain Occurring Later Inmentioning
confidence: 99%
“…This is important as descending serotonergic RVM-spinal dorsal horn have been reported to act in a facilitatory way in neonates ( 26 ). In addition, the anti-nociceptive effect of 5-HT1aR becomes more apparent from postnatal day 4 onwards, and this coincides with progressive increase in acute hypersensitivity with cumulative exposure to repetitive needle pricking ( 14 16 , 23 ). 5-HT1aR in neonates inhibit nociceptive signaling through a reduced glutamate release from primary afferent terminals or by increasing the incidence of long-term depression induced inhibition of postsynaptic dorsal horn responses ( 28 , 29 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 97%
“…A separate litter was left completely undisturbed (UC; n = 10). Rat pups (conditions 1–3) were noxiously stimulated with repetitive needle pricks (NP) four times a day at 09:00 a.m., 10:00 a.m., 11:00 a.m. and 12:00 p.m. from P0 to P7 as previously described ( 13 , 14 ). Each noxious stimulation consisted of a single 2 mm deep needle prick with a 25G needle in the mid-plantar surface of the left hind paw.…”
Section: Methodsmentioning
confidence: 99%